Representasi Identitas Kota Musik Dunia dalam Film Dokumenter “Nada Nusantara Ambon" - Latumanuwy, Bryan Fardy; Sukendro, Gregorius Genep (Kiwari, 2025)
The documentary film Nada Nusantara Ambon represents Ambon's identity as a World City of Music, recognised by the UNESCO Creative Cities Network since 2019. This study analyses the representation of Ambon's identity through symbols of traditional music culture using Roland Barthes' semiotic approach. The conceptual basis of the study is grounded in Stuart Hall's theory of representation and Kavaratzis' theory of city identity, which emphasises the construction of a city's image and meaning through cultural and symbolic practices. This study uses a descriptive qualitative method with data collection techniques in the form of observation and documentation of films. The analysis was carried out in stages of denotative and connotative meaning to reveal the ideology hidden behind visual signs and narratives. The results show that the film Nada Nusantara Ambon represents the city's identity through the visualisation of traditional musical instruments, cultural narratives, and the social symbol of pela gandong, which emphasises the values of brotherhood and harmony. This representation not only highlights the richness of local culture but also builds the collective identity of the Ambon community, which supports cultural preservation and strengthens the city's branding as a World City of Music at the global level. Film dokumenter Nada Nusantara Ambon merepresentasikan identitas Ambon sebagai Kota Musik Dunia yang diakui dalam jejaring kota kreatif UNESCO sejak 2019. Penelitian ini menganalisis representasi identitas Kota Ambon melalui simbol-simbol budaya musik tradisional dengan menggunakan pendekatan semiotika Roland Barthes. Landasan konseptual penelitian bertumpu pada teori representasi Stuart Hall dan teori identitas kota dari Kavaratzis yang menekankan konstruksi citra dan makna kota melalui praktik budaya dan simbolik. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data berupa observasi dan dokumentasi terhadap film. Analisis dilakukan dengan tahapan makna denotatif dan konotatif untuk mengungkap ideologi yang tersembunyi di balik tanda visual dan narasi. Hasil penelitian menunjukkan bahwa film Nada Nusantara Ambon merepresentasikan identitas kota melalui visualisasi alat musik tradisional, narasi budaya, serta simbol sosial pela gandong yang menegaskan nilai persaudaraan dan harmoni. Representasi tersebut tidak hanya menonjolkan kekayaan budaya lokal, tetapi juga membangun identitas kolektif masyarakat Ambon yang mendukung pelestarian budaya dan memperkuat branding kota sebagai Kota Musik Dunia di tingkat global.